Leveraging Local Expertise in Stewardship, Hospital Epidemiology and Public Health to Enrich Postgraduate Training in NYC. (October 2020) - Cowman, Kelsie; Ostrowsky, Belinda; Seo, Susan; Chen, Victor; Bartash, Rachel; Nori, Priya
Abstract : Background: New York City is a gateway for emerging pathogens and global threats. In 2013, faculty from Montefiore Medical Center and Memorial Sloan Kettering developed a free half-day workshop for postgraduate trainees in antimicrobial stewardship (AS), infection prevention (IP), hospital epidemiology, and public health. This annual workshop, sponsored by the Infectious Diseases Society of New York (IDSNY), incorporates case studies and expert panel discussions on timely topics such as Ebola, Candida auris, Clostridiodes difficile, measles, nosocomial influenza, drug shortages, and AS/IP "big data." Methods: From 2013 through 2017, the workshop involved 10–15 interactive AS/IP cases with audience response questions and panel discussions. In 2018–2019, based on feedback, the format was revised to emphasize breakout sessions in which participants actively practiced AS/IP tools, (eg, medication utilization evaluations, epidemiologic curves, and performance improvement devices). Examples of 2018–2019 cases are shown in Figure 1. A pre- and postseminar paper survey was conducted yearly to understand baseline training in AS/IP, desire for future AS/IP careers, and self-reported effectiveness of the workshop. Results: Initially, the primary audience was NYC ID fellows. From 2018 onward, we opened enrollment to pharmacy residents. Approximately 45 NYC ID fellows were eligible for the course each year. Results from 2013 to 2016 surveys were reported previously (Fig. 2). There were 32 attendees in 2018, 42 in 2019. The survey response rate was 88% in 2018 and 95% in 2019, with 68 (92%) total participants. Most participants had received previous training in IP (82%) and AS (94%) (Fig. 3). Most participants reported that the program was a good supplement to their ID training (98%) and that case studies were an effective means of learning IP (100%) and AS (98%). Furthermore, 92% stated they would like additional AS/IP training, and many since 2013 have requested a full-day course. Self-reported interest in future involvement in AS/IP increased after the workshop: IP, 68%–83% ( P =.04) and AS, 88%–91% ( P = .61). Conclusions: Most trainees reported satisfaction with the workshop and case-study learning method; interest in future AS/IP careers increased after the seminar. We intend to explore Funding: to expand to a full-day program for all NYC postgraduate trainees and AS/IP junior faculty. As such, we hope to obtain the endorsement of professional societies such as SHEA. This workshop could address a crucial educational gap in AS/IP postgraduate training and help sustain our future workforce. Funding: None Disclosures: None